Does the maternal age affect the mesenchymal stem cell markers and gene expression in the human placenta? What is the evidence?. Issue 4 (August 2015) - Alrefaei, Ghadeer Ibrahim; Al-Karim, Saleh; Ayuob, Nasra Naeim; Ali, Soad Shaker
Highlights CD105 expression in placental MSCs negatively correlated with the maternal age. CD29 expression in placental MSCs negatively correlated with the maternal age. CD105 MSCs are significantly abundant in the decidua basalis and placental villi. CD29 MSCs are significantly abundant in the decidua basalis and placental villi.